Remote intelligent concentration measurement of gas dissolved in water - Machekhin, Yu. P.; Kuhtin, S. K. (Journal of Physics, 2010)
Introduction of fibre optic based systems, operating on the principle of optical spectroscopy allow remote intelligent sensing and concentration measurement of gasses dissolved in water on a great depth. Among all spectroscopic methods, Raman spectroscopy is one of the most widespread techniques for gas detection in water. However, high cost of devices operating on this principle significantly limits its application. Laser modulation spectroscopy is another good technique which can be applied to reduce cost of water monitoring devices and provide accurate concentration measurements in water. This thesis describes principle of remote gas detection via intelligent fiber optic sensing system which operates on the principle of modulation laser spectroscopy and its feasibility for measurements in water.
Keywords: optical spectroscopy; modulation; fibre optic